👤

Descompune in factori a) (x-1)(x+4)-(x-1) la pătrat -3(x-1) alt exercitiu (a-b)(x+3)+(b-a)(2x-1)-(a-b)(x+7) alt exercitiu (x+1)(x-4)+(4-x)(x+2)-x(x-4) alt exercitiu (2x-1)(x+5)+(2x-1) la pătrat -2x la pătrat +x

Răspuns :

(x-1)(x+4)-(x-1)² -3(x-1)=(x-1)(x+4-x+1-3)=2(x-1)

(a-b)(x+3)+(b-a)(2x-1)-(a-b)(x+7)=(a-b)(x+3)-(a-b)(2x-1)-(a-b)(x+7)=
=(a-b)(x+3-2x+1-x-7)=(a-b)(-2x-3)=

(x+1)(x-4)+(4-x)(x+2)-x(x-4)  =(x+1)(x-4)-(x-4)(x+2)-x(x-4)  =
=(x-4)(x+1-x-2-x)  =(x-4)(-1-x)  =(4-x)(1+x)

(2x-1)(x+5)+(2x-1)² -2x²+x =
=(2x-1)(x+5)+(2x-1)² -x(2x-1) =
=(2x-1)(x+5+2x-1 -x) =
=(2x-1)(2x+4) =2(2x-1)(x+2)